Theoretical Analysis and Experimental Validation of the Scholte Wave Propagation in Immersed Plates for the Characterization of Viscous Fluids - Takiy, A. E. [UNESP]; Granja, S. C. G. [UNESP]; Higuti, R. T. [UNESP]; Kitano, C. [UNESP]; Elvira, L.; Martinez-Graullera, O. F.; Montero de Espinosa, F.; IEEE (Ieee, 2013)
This work reports the study of an attractive interfacial wave for application in ultrasonic NDE techniques for inspection and fluid characterization. This wave, called quasi-Scholte mode, is a kind of flexural wave in a plate in contact with a fluid which presents a good sensitivity to the fluid properties. In order to explore this feature, the phase velocity curve of quasi-Scholte mode is experimentally measured in a plate in contact with a viscous fluid, showing a good agreement with theory.
Keywords: interfacial wave; fluid characterization; bulk longitudinal velocity; viscous fluid